Paternal genetic structure in contemporary mennonite communities from the American midwest - Beaty, K.; Mosher, M.; Crawford, M.; Melton, Phillip (2016)
© 2017 Wayne State University Press. Over the last 35 years, researchers from the Laboratory of Biological Anthropology at the University of Kansas have been working with Mennonite communities to better understand evolutionary patterns of fission-fusion in relationship to their genetic history and population structure. In this study, short tandem repeat (STR) markers from the nonrecombining region of the Y chromosome (NRY) provided increased resolution of the molecular population structure for these groups. NRY is known to be informative for determining paternal genetic ancestral patterns in recently derived human populations. Mennonites represent a branch of the Anabaptist movement that began in northern and central Europe in the 16th century and maintain a well-documented migration and genealogical history. Provided this historical information, we investigated the genetic relationship of 15 NRY STR loci within five Mennonite communities from Kansas (Goessel, Lone Tree, Garden View, and Meridian) and Nebraska (Henderson). We sought to determine if patterns of fission/fusion along familial lines persisted with paternal genetic information as evidenced through other classical genetic polymorphisms and molecular markers. NRY haplotype information was obtained for 94 individuals, and genetic variation was analyzed and compared across the five study populations and comparative Anabaptist and European populations. NRY haplogroups were assigned using a Bayesian allele frequency approach with 14 STR loci. A total of 92 NRY haplotypes were detected, with none shared across these communities. The most prevalent NRY haplogroup was R1b, which occurred in 56% of the entire sample. Eight additional NRY haplogroups (E1b1b, G2a, I1, I2, J2a1, L, Q, and R1a) were detected in smaller frequencies. Principal component analysis of NRY data, in contrast to mitochondrial DNA data, displayed no patterns of population subdivision of these congregations into communities. These NRY genetic profiles provide additional information regarding the recent migratory history of Mennonite communities and additional evidence for fission along paternal lines after migration to the United States.